Public preferences for delayed or immediate antibiotic prescriptions in UK primary care: a choice experiment - Morrell, E; Buchanan, J; Roope, L; Pouwels, K; Butler, C; Tonkin-Crine, S; Walker, S; Wordsworth, S (Public Library of Science, 2021)
Background: Delayed (or ‘back-up’) antibiotic prescription, where the patient is given a prescription but advised to delay initiating antibiotics, has been shown to be effective in reducing antibiotic use in primary care. However, this strategy is not widely used in the UK. This study aimed to identify factors influencing preferences among the UK public for delayed prescription, and understand their relative importance, to help increase appropriate use of this prescribing option. Methods and Findings We conducted an online choice experiment in two UK general population samples: adults, and parents of children under 18 years. Respondents were presented with twelve scenarios in which they, or their child, might need antibiotics for a respiratory tract infection, and asked to choose either an immediate or a delayed prescription. Scenarios were described by seven attributes. Data were collected between November 2018 and February 2019. Respondent preferences were modelled using mixed-effects logistic regression. The survey was completed by 802 adults and 801 parents (75% of those who opened the survey). The samples reflected the UK population in age, sex, ethnicity and country of residence. The most important determinant of respondent choice was symptom severity, especially for cough-related symptoms. In the adult sample the probability of choosing delayed prescription was 0.53 (95% CI 0.50-).56, p<.001) for a chesty cough and runny nose, compared to 0.30 (0.28-0.33, p<.001) for a chesty cough with fever, 0.47 (0.44-0.50, p<.001) for sore throat with swollen glands and 0.37 (0.34-0.39, p<.001) for sore throat, swollen glands and fever. Respondents were less likely to choose delayed prescription with increasing duration of illness (odds ratio 0.94 (0.92-0.96, p<0.001)). Probabilities of choosing delayed prescription were similar for parents considering treatment for a child (44% of choices vs. 42% for adults, p=0.04). However, parents differed from the adult sample in showing a more marked reduction in choice of the delayed prescription with increasing duration of illness (OR 0.83 (0.80-0.87) vs 0.94 (0.92-0.96) for adults, p for heterogeneity <0.001), and a smaller effect of disruption of usual activities (OR 0.96 (0.95-0.97) vs. 0.93 (0.92-0.94) for adults, p for heterogeneity <0.001). Females were more likely to choose a delayed prescription than males for minor symptoms, particularly minor cough (probability 0.62 (0.58-0.66, p<0.001) for females, 0.45 (0.41-0.48, p<0.001) for males). Older people, those with a good understanding of antibiotics, and those who had not used antibiotics recently, showed similar patterns of preferences. Study limitations include its hypothetical nature, which may not reflect real-life behaviour; the absence of a “no prescription” option; and the possibility that study respondents may not represent the views of population groups who are typically under-represented in on-line surveys. Conclusion This study found that delayed prescription appears to be an acceptable approach to reducing antibiotic consumption. Certain groups appear to be more amenable to delayed prescription, suggesting particular opportunities for increased use of this strategy. Prescribing choices for sore throat may need additional explanation to ensure patient acceptance, and parents in particular may benefit from reassurance about the usual duration of these illnesses.